QUESTIONS OF INFORMATIONAL SECURITY OF KHERSON STATE UNIVERSITY (Journal of Information Technologies in Education (ITE), 2009)
The article deals with problems of informational security of modern organizations and analyzes relevant questions of computer security at Kherson State University.
Keywords: computer; informational; IT; security